Do males measure body sizes of males and females similarly? A test in the beaugregory damselfish, Stegastes leucostictus. Issue 2 (4th March 2017) - Bloch, A.N.; Paciorek, T.; Richter, M.; Itzkowitz, M.
Abstract : Body length in fishes appears to serve as a "signal" for intra-sexual selection (i.e., male–male competition) and inter-sexual selection (i.e., mate choice). Previous studies indicate that the size of males correlates with the ability to gain or control resources from other males, while the size of females corresponds to features related to reproductive success such as fecundity. However, it remains unclear whether male size, as it relates to success in territory defense, is assessed similarly to female size as it relates to fecundity. Using the beaugregory damselfish ( Stegastes leucostictus ), a Caribbean coral reef fish, we examined whether focal males measure the "signal", body length, similarly in both sexes. We presented focal territorial males with pairs of males and pairs of females that differed in size by varying degrees, and judged whether the focal male used size to differentiate between the two stimuli. We found that focal males did respond differently based on sex (spent more time near the two male stimuli) and size (spent more time near the larger fish) but did not respond to size differences based on sex. Thus, focal males measured size differences in both sexes similarly in spite of the size reflecting different attributes in males and females.